Theoretical analysis of grouting reinforcement for surrounding rock of deep shaft based on stability and water inflow control - Xiang, Peng; Ji, Hong Guang; Zhang, Guang Quan; Li, Wen Guang (Frontiers in Earth Science, 2023)
To address the challenge of designing grouting reinforcement in a deep shaft to control water, this study established an elastic-plastic analytical formula for the grouted rock surrounding a shaft under the combined action of thermal, hydraulic, and mechanical fields based on the Mohr–Coulomb yield criterion. The various rules and influencing factors of stability and impermeability of the grouted rock surrounding the shaft are calculated and analyzed. The analysis shows that damage to the surrounding rock is aggravated by the action of high ground temperature and high water pressure in deep shafts, and the influence of water pressure is particularly significant. The larger the radius and cohesion of the grouted surrounding rock, the smaller the radius of its plastic zone. With an increase in the elastic modulus ratio between the grouted surrounding rock and the original rock, the radius of its plastic zone increases, so the elastic modulus of the grouted surrounding rock design should consider the original surrounding rock. With a decrease in the permeability coefficient of the grouted surrounding rock, the radial stress decreases, the tangential stress increases, and the radius of the plastic zone increases. The development of plastic zone not only affects the stability but also causes an increase in the permeability coefficient. There is mutual restriction and influence between the shaft water inflow, the permeability coefficient, the radius of the grouted surrounding rock, and the radius of its plastic zone. In the design of grouting reinforcement, the stability of surrounding rock and the control requirements of shaft water inflow should be comprehensively considered and the optimal parameters should be selected based on theoretical calculation. This study provides a theoretical basis for the optimization of grouting reinforcement parameters in a deep shaft.